Neonatal Problems and Infancy Growth of Term SGA Infants: Does "SGA" Definition Need to Be Re-evaluated? - Saygin Abali; Serdar Beken; Eda Albayrak; Aysegul Inamlik; Burcu Bulum; Ezgi Bulbul; Gulten Zeynep Eksi; Zeynep Alize Ay; Melis Karabay; Didem Kaya; Muge Halici; Serap Semiz; et al. (Frontiers Media S.A., 2021)
Introduction: The exact definition of small-for-gestational-age (SGA) infant is still controversial among clinicians. In this study, we aimed to understand which definition is better in terms of establishing both early postnatal problems and growth. In this way, we compared early neonatal problems and infancy growth of term infants with birth weight (BW) < -2 SDS and with BW between 10th percentile (−1.28 SDS) and −2 SDS.Methods: A single center retrospective cohort study was conducted. Preterm infants, multiple gestations and newborns with any congenital anomalies were excluded from the study. Study group was defined as Group 1 (n = 37), infants BW < −2.00 SDS; Group 2 (n = 129), between −1.28 and −2.00 SDS; and Group 3 (n = 137), randomly selected newborns with optimal-for-gestational-age (BW between −0.67 and +0.67 SDS) as a control group.Results: The incidence of severe hypoglycemia was highest in Group 1 (%10.8) and Group 2 and 3 had similar rates of severe hypoglycemia (0.8 and 0.7%, respectively). The incidence of polycythemia was 5.4% in Group 1 and was significantly higher than Group 3 (0.0%) while it was 2.3% in Group 2. Short stature (length < −2 SDS) ratio at the age of 1 and 2 years were similar in each group. Overweight/obesity ratio at the age of 1 were 9.5, 20.8 and 16.7% in each group, respectively (p = 0.509).Conclusion: This study was planned as a pilot study to determine potential differences in the problems of hypoglycemia, polycythemia, and growth according to the differences in definition. Short term disturbances such as hypoglycemia and polycythemia are found to be higher in infants with a BW SDS below −2. From this point of view, of course, it will not be possible to change the routine applications immediately, however this study will be an initiative for discussions by making long-term studies.